An exploration of women's perceptions of their right to choose place of childbirth in Cyprus. A phenomenological study - Hadjigeorgiou, Eleni; Kouta, Christiana; Papastavrou, Evridiki; Papadopoulos, Irena (My University, 2012)
Background: Childbirth is one of the most important events in a woman's life. The place of birth is considered to be a crucial factor for a positive maternity experience. Aim: To investigate women's perceptions of their right to choose their place of childbirth in Cyprus. Method: A qualitative study was conducted using a phenomenological approach, with the use of interviews with women (n=48), and two focus groups (n=13). The sampling was purposive. Data analysis followed Colaizzi's steps. Results: Four themes emerged: (a) Birth place choices, (b) the relationship between women and health professionals, (c) the continuity of perinatal care, and (d) the safety of the mother and her newborn child. The choice of home birth was rejected by 58 women (95%). Most women (79%) expressed interest in giving birth in birth centres and urged remedy of the conditions in public and private hospitals. Conclusions: The right of Cypriot women for birth place choice is not guaranteed. This study can be considered innovative for Cyprus, because it is the first time that perceptions of Cypriot women in relation to maternal care have been researched. This will enable maternal care evidenced-based interventions to be designed that take into consideration women's needs.
Keywords: Birth centre; Home birth; Hospital birth; Informed choices; Medicalization; Midwifery model; Place of birth